Inflammatory Bowel Disease and Risk of Birth Defects in Offspring. (7th January 2020) - Auger, Nathalie; Côté-Daigneault, Justin; Bilodeau-Bertrand, Marianne; Arbour, Laura
Abstract: Background and Aims: The relationship between inflammatory bowel disease in pregnancy and birth defects is not understood. We evaluated whether Crohn's disease and ulcerative colitis in pregnant women were associated with the risk of birth defects in the offspring. Methods: We undertook a retrospective cohort study of 2 184 888 pregnancies in Quebec, Canada, between 1989 and 2016. We calculated risk ratios [RR] and 95% confidence intervals [CI] for the association between inflammatory bowel disease and the risk of birth defects, using generalised estimating equations adjusted for maternal characteristics. We assessed associations in the period before 2000, when immunosuppressive biologic therapy and folic acid food fortification were not yet available, compared with the period after 2000 when these interventions were more widespread. Results: This study included 13 099 women with Crohn's disease and 7798 with ulcerative colitis. Crohn's disease was associated with 1.90 times [95% CI 1.10–3.28] the risk of abdominal wall defects [gastroschisis, omphalocoele, and diaphragmatic hernia] and ulcerative colitis was associated with 1.53 times [95% CI 1.02–2.30] the risk of central nervous system defects. The association of Crohn's disease with abdominal wall defects was stronger before 2000 [RR 3.62, 95% CI 1.71–7.67] than after 2000 [RR 1.23, 95% CI 0.55–2.75]. Ulcerative colitis was associated with central nervous system defects regardless of time period. Conclusions: These findings suggest that inflammatory bowel disease is associated with the risk of abdominal wall and central nervous system defects, and that introduction of immunobiologic medications is unlikely to be associated with added risk. Podcast: This article has an associated podcast which can be accessed at https://academic.oup.com/ecco-jcc/pages/podcast